2005
DOI: 10.1016/j.actaastro.2005.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of spatial structure of human proximal tibial bone biopsies using 3D measures of complexity

Abstract: Changes in trabecular bone composition during development of osteoporosis are used as a model for bone loss in microgravity conditions during a space flight. Symbolic dynamics and measures of complexity are proposed and applied to assess quantitatively the structural composition of bone tissue from 3D data sets of human tibia bone biopsies acquired by a micro-CT scanner. In order to justify the newly proposed approach, the measures of complexity of the bone architecture were compared with the results of tradit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…The higher bone fills observed by Virolainen et al may be explained by differences in defect type (unicortical vs. transcortical defects), surgical site (tibia vs. cranium) and bone quantification techniques (histomorphometry vs. micro‐CT). Bone quantification by micro‐CT has been shown to represent a reliable and fast approach for imaging and quantifying bone formation (Uchiyama et al 1997; Langheinrich et al 2005; Recker et al 2005; Saparin et al 2005) (Muller et al 1998). In this study, 110 cross‐sectional images were reconstructed and analysed for each cranial defect, thereby producing a better representation of the bone volume than the one extrapolated from a limited number of cross sections analysed in histomorphometric studies.…”
Section: Discussionmentioning
confidence: 99%
“…The higher bone fills observed by Virolainen et al may be explained by differences in defect type (unicortical vs. transcortical defects), surgical site (tibia vs. cranium) and bone quantification techniques (histomorphometry vs. micro‐CT). Bone quantification by micro‐CT has been shown to represent a reliable and fast approach for imaging and quantifying bone formation (Uchiyama et al 1997; Langheinrich et al 2005; Recker et al 2005; Saparin et al 2005) (Muller et al 1998). In this study, 110 cross‐sectional images were reconstructed and analysed for each cranial defect, thereby producing a better representation of the bone volume than the one extrapolated from a limited number of cross sections analysed in histomorphometric studies.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we use recently developed structural measures of complexity (SMC) ] as an evaluation tool to quantify different aspects of the bone architecture and its evolution along the simulation of the bone mass loss. This approach demonstrates also the efficiency of these SMC ; Gowin et al, (1998Gowin et al, ( , 2001; Saparin et al, (2004)] to evaluate changes in a bone architecture.…”
Section: Introductionmentioning
confidence: 81%
“…Following this fact, in 3D the symbol encoding is based on an alphabet of three different symbols [Saparin et al, (2004)], which represent marrow M , bone surface (one voxel thick) S, and internal bone I. Three measures have been applied to quantify the bone image: Structure Complexity Index (SCI 3D), and a normalized probability density of the trabecular surface P (S), and internal bone P (I) voxels inside the bone image.…”
Section: Modeling Algorithmsmentioning
confidence: 99%
“…More recently developed methods for quantifying the complexity of trabecular structures includes methods using measures of complexity based on symbolic dynamics (Saparin et al, 1998;Saparin et al, 2005), fractal properties (Marwan et al, 2007b) and on recurrence (Marwan et al, 2007a), or using volumetric spatial decompositions (Stauber and Müller, 2006). By applying these approaches to 3D images of trabecular bone, it was shown that the bone microarchitecture changes substantially during the development of osteopenia/osteoporosis.…”
Section: Introductionmentioning
confidence: 99%
“…By applying these approaches to 3D images of trabecular bone, it was shown that the bone microarchitecture changes substantially during the development of osteopenia/osteoporosis. The main conclusions in (Saparin et al, 2005;Marwan et al, 2007a) were that the complexity of the bone microarchitecture decreases with increasing bone loss and that the volume and surface of the trabecular structure changes in a different amount. This latter conclu-sion confirms former findings that the shapes of the trabeculae change during bone loss, e. g., from platelike structure to rod-like structure (Hildebrand et al, 1999).…”
Section: Introductionmentioning
confidence: 99%